INPUTS COST SENSITIVITY ANALYSES OF BETEL LEAF PRODUCTION: A STUDY ON SELECTED FARMERS AT THE DISTRICTS OF KUSHTIA-JHENIDAH IN BANGLADESH - Sabur, Md. Abdus; Rahman, Md. Mizanoor; Sina, Md. Abu; Huda, Md. Nazmul; Uddin, Md. Kamal (International Journal of Research -GRANTHAALAYAH, 2022)
The study aims to evaluate the inputs cost sensitivity of betel leaf production of selected farmers in Bangladesh. Purposively two districts like Kushtia and Jhenidah were chosen for study area. Both primary and secondary data were used for the purpose of the study. Primary data were collected from 120 farmers. For analyzing data 9 variables were used like Material cost, Labor, Land cost(Lease), Fertilizer, Insecticide, Irrigation Cost, Depreciation of Primary cost, Selling and Distribution cost, Other cost as input costs and one variable(Sales) was used as output variable. The analysis have been done by applying descriptive statistics, Cobb-Douglas production function and marginal physical productivity (MPP) to identify nature of production function and influential sensitive input costs. The summation of all regression co-efficient included in the model, ∑βi=1.35 indicated that the production function is in the state of increasing return to scale. The highest MPP value was found in other cost (64.95) followed by insecticide (3.22); selling and distribution cost (2.69); labor cost (1.25) and fertilizer (1.20) which are very sensitive inputs and have the strong influence on output variables.